The application of the PLUS model in a prison library: An information literacy microteaching - Chrysanthopoulos, Christos; Koulouris, Alexandros; Kouis, Dimitrios; Efthymiou, Foteini (Journal of Integrated Information Management, 2024)
Purpose – This article aims to detail a plan for the application of the PLUS information literacy model in the context of a prison library. A brief overview of the literature will highlight the importance of (co-)developing activities based on multiple models and learning theories. At the same time, the article argues in favour of the idea that the implementation of information literacy programmes in the context of excluded and socially vulnerable groups can substantially help to improve their self-image and their smooth integration within the restrictive walls of the prison, as well enhancing their capability of returning to society and functioning as law-abiding members. Design/methodology/approach - The research hypothesis for the project is situated within the context of a prison library. There, the educator teaching the subject of Sociology (Social Literacy) at the Second Chance School (SCS), will express their wish that each learner prepares a presentation - on the subject of discrimination (e.g. gender, political beliefs, religion, social exclusion, minorities, etc.). To this end, the educator will propose that learners seek guidance from the librarian on a topic pertinent to the concept of discrimination (racism). The approach followed by learners when preparing their presentation will be based on the PLUS model of information literacy. Methodologically, the study is based on the synthesis of fundamental theories of adult education with the PLUS information literacy model. Findings - The development of work plans in an informational organisation environment, inspired by microteaching, can serve as a good example for promoting the application of informational models to their operation and services. Originality/value - There are few examples of applications of informational models in educational processes for socially vulnerable or excluded groups. This article also enhances awareness on issues pertaining to libraries and education within prisons not just in Greece, but also abroad.